A Comparative Study of Profitability of Agricultural Cooperatives in Poland and Around the World - Małgorzata Matyja (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The differences in perception and functioning of agricultural cooperatives in different parts of the world are visible to the naked eye. Moreover, the literature brings different findings in respect to comparisons between cooperatives and non-cooperatives in terms of profitability. The purpose of this article was to identify the differences in profitability between agricultural cooperatives in selected parts of the world as well as between cooperatives and other enterprises in Polish agriculture. The description of results of the world report on cooperatives and analysis of variance on 300 agricultural enterprises in Poland were used in order to accomplish the above purpose. The main findings prove that American agricultural cooperatives achieved the best profitability results and that cooperatives have lower profitability than other enterprises in agriculture.